Abundance, Diversity and Distribution of Mollusca in the Gharaf River, Southern Iraq - Mirza, Nada N. A.; Nashaat, Muhanned Remzi (Iraqi Journal of Science, 2019)
This study is based on samples taken from one of the main branches of Tigris River; Gharaf River, at Kut Barrage in Wasit Governorate, Iraq. It aimes to study the quantity and quality of the mollusca Invertebrates; furthermore. The study evaluates the molluscan biodiversity of the rivers by using appropriate biodiversity indexes. Thus, the first of its kind study in the evaluation of the diversity of mollusc in Gharaf River assemblage. Monthly samples were collected randomly from the river mud, for 12 months, from January till December 2016. During the collection process; 5 stations on the river were chosen for sampling with 10(Â±1) Km distance between each of the stations, including Wasit Governorate. The study showed the presence of 20 Molluscs species were recorded for the first time in Gharaf River. In terms of population density, the annual average for Molluscs was 686.34 Ind./m2 . Relative Abundance Index (Ra) showed that Melanoid tuberculate, Physa acuta and Lymnaea auricularia was less abundant species in Gharaf River. According to the Constancy Index (S) Corbicula fluminalis, M. tuberculata, M. nodosa, Theodoxus jordani, L. auricularia and Physa acuta considered as constancy species in Gharafâ€™s environment. The highest recorded values of the Species Richness index were 0.0303, while the lowest values were a complete absence (zero). Regarding Jaccard Presence-Community, the results demonstrated that the highest similarity percentage between mollusca communities in Gharraf River was between stations 3 and 5, recorded at 66.66%. In the case of the Shannon-Weiner Diversity Index (H), the diversity values in Gharaf peaked at 7.819 bit/Ind. and a complete absence (zero) at its lowest point. However, the Species Uniformity Index (E) results revealed the highest uniformity values was 1, while, the lowest values were complete absence (zero).